2023
DOI: 10.3390/su15043017
|View full text |Cite
|
Sign up to set email alerts
|

A Software Framework for Predicting the Maize Yield Using Modified Multi-Layer Perceptron

Abstract: Predicting crop yields is one of agriculture’s most challenging issues. It is crucial in making national, provincial, and regional choices and estimates the government to meet the food demands of its citizens. Crop production is anticipated based on various factors such as soil conditions and meteorological, environmental, and crop variables. This study intends to develop an effective model that can accurately anticipate agricultural production in advance, assisting farmers in better planning. In the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The adjusted parameters determine how well the actual outcome matches the original specification. Following this calculation, the node may utilise the result of equation (9) [44] to evaluate the predicted output of the MLP network for, O .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted parameters determine how well the actual outcome matches the original specification. Following this calculation, the node may utilise the result of equation (9) [44] to evaluate the predicted output of the MLP network for, O .…”
Section: Resultsmentioning
confidence: 99%
“…The S h notation represents the neuron's output. The whole result may be calculated using equation (10) [44,45]. Based on the estimated loss, which is determined using equation (11), the network modifies the input neuron weights, the hidden node weights in the output layer, and the predicted value ( ) y .…”
Section: Resultsmentioning
confidence: 99%
“…Comparative metrics for assessing model robustness in grain yield prediction in terms of R 2 , MAE, RMSE and n-RMSE are shown in Figure 5. Ensemble algorithms demonstrated superior performance in crop yield prediction (Ahmed, 2023), while RF is the optimized algorithm for accurately forecasting maize yields at the county level through the integration of diverse data sources (Pham and Olafsson, 2018). Aqil et al (2022) reported that incorporating ensemble machine learning may enhance the accuracy of classifying maize plants.…”
Section: Assessment Of Ml-ga and Ensemble ML Performances On Grain Yi...mentioning
confidence: 99%
“…Regardless, our established model yielded more accurate predictions compared to their findings. Furthermore, recent research conducted by Ahmed [120] to predict maize yield in the Saudi Arabia region based on weather data has further proven the potential of XGBoost in enhancing estimation accuracy compared to GBM. The study noted a decrease in RMSE value by 0.01 t/ha, indicating the improved performance of XGBoost in accurately predicting crop yield.…”
Section: Accuracy Assessment and Influence Of Featuresmentioning
confidence: 99%